PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MATERI PERSEGIPANJANG DAN PERSEGI SETTING KOOPERATIF YANG MELIBATKAN TEORI BRUNER PADA KELAS VII MTs NEGERI BONTOTANGGA - Irfawanndi Samad; Muhammad Darwis M; Alimuddin Alimuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
This is a development research focuses on developing mathematics learning tools of cooperative setting using Bruner theory. Learning instruments on this research include students’ book, studens worksheet, lesson plan, learning outcomes test of students in class VIIe of MTs. Negeri Bontotangnga. It used a Thiagarajan model (4-D) which consisted of several phases, namely define, design, develop, and disseminate. The developed learning tools were validated by two experts by the result of valid and 2 observers by the result on the good category. The trial was conducted in MTs. Negeri Bontotangnga by number of students were 25 people. The result of showed that the learning tools have fulfilled the criteria of practical and was classified on good category. The field trial revealed that the learning tools have fulfilled the criteria of effective, those are: (1) mathematics learning outcomes has fulfilled the minimum mastery criteria as much 88%, and directly the classical mastery also fulfilled; (2) students’ activities were run as expected; (3) students’ responses has fulfilled the criteria of positive response. Based on thet result, it can be concluded that mathematics learning tools of cooperative setting using Bruner theory fulfilled the criteria of valid, practical, and effective.